Extended-Interval Dosing of Aminoglycosides in Pediatrics: A Narrative Review - Ebrahim Salehifar; Mohammad Reza Rafati (Mazandaran University of Medical Sciences, 2015)
Aminoglycosides (AGs) are frequently used in pediatric settings, especially for empiric treatment of early-onset neonatal sepsis. Although AGs are used for several decades, the optimum method of administration and their dosing schemes needs more clarification. The risks of ototoxicity and nephrotoxicity, two main toxicities associated with AGs, have been contributed to the peak and trough plasma levels, respectively. One approach to decrease these potential toxicities of AGs is to administer higher doses with a prolonged interval, named extended-interval dosing (EID). Post-antibiotic effect (PAE) and concentration-dependent killing of AGs provide rational basis for the efficacy of EID. PAE refers to the extended bactericidal activity of AGs against many Gram-negative organisms after the drug was removed by metabolism. One concern is that the higher initial peak concentration with EID may be accompanied with more toxicities, especially ototoxicity. It was demonstrated that due to saturation of binding site of AGs in renal and cochlear tissues, transiently higher concentration of AGs does not cause additional nephrotoxicity or ototoxicity. Experience and clinical evidence regarding EID in pediatrics is suboptimal. In this review, we presented the rational and studies focusing on EID in pediatric setting. The overall finding of trials is that in pediatric setting, EID is a safe and effective dosing method. The risk of serum drug concentration outside the therapeutic range is lower in neonates treated with EID, leading to less need of therapeutic drug monitoring (TDM) with EID. Moreover, there are evidences supporting lower chance of bacterial resistance with EID compared with traditional dosing approach.